Iowa TelePrEP: A Public-Health-Partnered Telehealth Model for Human Immunodeficiency Virus Preexposure Prophylaxis Delivery in a Rural State. Issue 8 (August 2019) - Hoth, Angela B.; Shafer, Cody; Dillon, Dena Behm; Mayer, Randy; Walton, George; Ohl, Michael E.
Abstract : Background: Access to human immunodeficiency virus (HIV) preexposure prophylaxis (PrEP) is often poor in small urban and rural areas because of stigma and long distances to providers. The Iowa Department of Public Health and The University of Iowa created a regional telehealth program to address these barriers ("Iowa TelePrEP"). We describe initial TelePrEP results and share lessons learned. Methods: Iowa Department of Public Health personnel in sexually transmitted infection (STI) clinics, disease intervention specialist and partner services, and HIV testing programs referred clients to pharmacists at University of Iowa. Clients could also self-refer via a website. Pharmacists completed video visits with clients in the community on smartphones and other devices, arranged local laboratory studies, and mailed medications. We performed a retrospective record review to quantify rates of PrEP referral, initiation, retention, guideline-concordant laboratory monitoring, and STI identification and treatment. Results: Between February 2017 and October 2018, TelePrEP received 186 referrals (37% from public health) and completed 127 (68%) initial video visits with clients. Median client age was 32; 91% were men who have sex with men. Most clients with video visits (91%) started PrEP. Retention in TelePrEP at 6 months was 61%, and 96% of indicated laboratory monitoring tests were completed. Screening identified 37 STIs (8 syphilis, 10 gonorrhea, 19 chlamydia). Disease intervention specialist and partner services linked all clients with STIs to local treatment within 14 days (80% in 3 days). Conclusions: Using widely available technology and infrastructure, public health departments and health care systems can collaborate to develop regional telehealth programs to deliver PrEP in small urban and rural settings. Abstract : Public health departments and a health care delivery system used widely available resources to create a collaborative, regional telehealth program to deliver human immunodeficiency virus preexposure prophylaxis.